Expert consensus on fetal ventriculomegaly: evidence-based recommendations for 23 key clinical questions - Li, Xin; Hu, Ting; Xiao, Xue (Frontiers in Pediatrics, 2025)
BackgroundFetal ventriculomegaly (VM), defined as an atrial diameter ≥10 mm, is one of the most frequently identified central nervous system anomalies on prenatal imaging. This expert consensus aims to address current gaps and inconsistencies in the prenatal diagnosis and management of fetal VM by providing evidence-based, graded recommendations across five key domains: diagnosis and etiology, systematic evaluation, antenatal management, delivery considerations, and short- and long-term prognosis.MethodsA multidisciplinary panel employed a modified Delphi method to formulate and refine 23 critical clinical questions. The process involved iterative rounds of expert consultation, structured questionnaires, and consensus building among specialists in obstetrics, fetal imaging, genetics, neonatology, neurology, rehabilitation, nursing, and informatics. Recommendations were informed by current international guidelines, high-quality cohort studies, and meta-analyses, and were graded using a modified GRADE framework to reflect the strength and quality of supporting evidence.ResultsKey recommendations include the standardized use of ultrasound and fetal MRI, the application of chromosomal microarray (CMA) in all VM cases regardless of isolation status, individualized monitoring protocols based on ventricular progression, and the need for structured neurodevelopmental follow-up in selected high-risk cases. Novel insights highlight the potential role of dynamic imaging parameters, maternal systemic factors, and emerging multi-omics tools in risk stratification and etiological investigation.ConclusionThis consensus provides a comprehensive, structured approach to fetal VM, promoting standardized clinical practice and facilitating early identification of high-risk fetuses. It emphasizes multidisciplinary decision-making and calls for future research into prognostic scoring systems, long-term outcomes, and novel etiological pathways.